Solve for x (with steps)(x – 4 )(3x + 2) = 0

(x – 4 )(3x + 2) = 0; x - 4 = 0; x = 4 3x + 2 = 0; 3x = -2; x = -2/3; x = 4 or x = -2/3

Question

Asked 3/5/2012 7:54:20 PM

Updated 9/5/2014 4:22:35 AM

1 Answer/Comment

Edited by andrewpallarca [9/5/2014 4:22:35 AM]

s

Rating

3

(x – 4 )(3x + 2) = 0;

x - 4 = 0; x = 4

3x + 2 = 0; 3x = -2; x = -2/3;

x = 4 or x = -2/3

x - 4 = 0; x = 4

3x + 2 = 0; 3x = -2; x = -2/3;

x = 4 or x = -2/3

Added 9/5/2014 4:22:26 AM

This answer has been confirmed as correct and helpful.

simplify: show steps (5x – 5 ) – ( 3x – 3) **Weegy:** (5x – 5 ) – ( 3x – 3), first we have to distribute the negative, so it becomes 5x - 5 - 3x + 3. You can skip this step, but we can pair up terms to get: 5x - 3x - 5 + 3. Subtract the 3x from the 5x to get: 2x - 5 + 3. Then add the 3 to the - 5 to get: 2x - 2. Your final answer is 2x - 2. (More)

Question

Expert Answered

Updated 5/21/2014 8:49:56 AM

0 Answers/Comments

simplify: show steps (5x^2 + 3x ) + ( 2x + 5) **Weegy:** First, get rid of the parentheses. 5x^2+3x+2x+5. Second, addition. 5x^2+5x+5 Third, divide everything by 5. x^2+x+5 (More)

Question

Expert Answered

Updated 5/21/2014 8:52:24 AM

1 Answer/Comment

To get the sum of (5x^2 + 3x ) + ( 2x + 5), combine like terms.

3x and 2x are the only like terms.

3x + 2x = 5x;

The answer is 5x^2 + 5x + 5

3x and 2x are the only like terms.

3x + 2x = 5x;

The answer is 5x^2 + 5x + 5

Added 5/21/2014 8:52:24 AM

This answer has been confirmed as correct and helpful.

simplify show steps(4x – 3.5) – (3x + 1.7) **Weegy:** First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer. (More)

Question

Expert Answered

Updated 5/21/2014 8:54:52 AM

1 Answer/Comment

(4x – 3.5) – (3x + 1.7), to get the difference,

4x - 3x = x;

-3.5 - 1.7 = -5.2

the answer is x - 5.2

4x - 3x = x;

-3.5 - 1.7 = -5.2

the answer is x - 5.2

Added 5/21/2014 8:54:51 AM

This answer has been confirmed as correct and helpful.

Simplify and show steps(8x – 2) + (7x + 6) **Weegy:** (8x – 2) + (7x + 6) = 8x - 2 + 7x + 6; = 8x + 7x - 2 + 6 = 15x + 4 (More)

Question

Expert Answered

Updated 7/15/2018 5:12:26 PM

0 Answers/Comments

Add (-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9) **Weegy:** 5x5= 25 (More)

Question

Expert Answered

Updated 8/5/2014 10:58:03 PM

1 Answer/Comment

31,220,274

questions answered

denyang

$172.20

Hearts 3,966 Views 968,506 Streams 470

phpmicro

$169.30

Hearts 3,573 Views 732,969 Streams 264

wildflower14344

$163.15

Hearts 3,627 Views 1,389,474 Streams 513

emdjay23

$152.05

Hearts 3,108 Views 646,790 Streams 229

maydj

$141.25

Hearts 3,364 Views 751,152 Streams 327

Flora1988

$113.90

Hearts 2,523 Views 354,475 Streams 172

miyaka

$110.00

Hearts 2,507 Views 460,154 Streams 327

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

There are no comments.